Ten Strategies for the Trinity: God as Transcendental Multiplicity and Ipsa Relationalitas - Migliorini, Damiano (Nuovo Giornale di Filosofia della Religione (NGFR), 2021)
's logical consistency. It is not my intention, however, to retrace here the salient points and studies of this debate (for several such overviews, see Morris, 1991, chap. 9; Inwagen, 1998; McCall & Rea, 2009; Damonte, 2009; McCall, 2010; Tuggy, 2003, 2016; Bertini, 2015). I recently proposed (Migliorini, 2019a) – after an evaluation of that debate – to consider the Trinitarian doctrine as contradictory, while also formulating an Argument (which I described as “Kantian-Inspired”) that should still allow us to believe in the Trinity. The Argument runs as follows: . . . .